Does outsourcing enable the survival of good care homes? A longitudinal analysis of all care homes in England, 2011–2023 - Anders Malthe Bach-Mortensen; Michelle Degli Esposti; Benjamin Goodair (BMJ Public Health)
Background It is unclear whether outsourcing has enabled the growth and survival of the best care homes, as intended. We aimed to test whether ownership (for-profit, public and third sector (non-profit)) influences determinants of closure among all care homes in England, 2011–2023.Methods We created a dataset of all care homes from 2011 to 2023 (29 548 care homes and 8346 closures) and Care Quality Commission inspections from 2014 to 2023 (n=65 726). Using logistic regression, we investigated determinants of care home closures including care home characteristics (eg, number of beds), service registrations (eg, dementia and nursing), quality (inspection ratings) and area deprivation. We then tested for interaction effects; specifically exploring (1) whether the determinants of closure vary by ownership and (2) whether quality differences between active and closed for-profit and third sector/public homes vary by area deprivation.Results The prevalence of for-profit care homes increased from 2011 to 2023. Ownership was a key determinant of care home closure; public and third sector care homes were almost twice as likely to close than for-profit providers (OR 1.8; 95% CI 1.44 to 2.24, p<0.001 and OR 1.6; 95% CI 1.37 to 1.76, p<0.001, respectively). Although care quality was also a significant determinant of closure, this association varied by care home ownership. For example, public and third sector homes rated ‘good’ were 7.6 percentage points (p<0.001) and 5.9 percentage points (p<0.001) more likely to close than for-profit homes with the same rating. Lastly, the quality of for-profit homes is heavily influenced by area deprivation, and the best active homes in deprived areas are operated by public and third sector providers.Conclusion Our findings suggest that outsourcing of care services has not promoted the survival of the best care homes and may have adverse effects on the equity and accessibility of care. This calls for a reassessment of current policies to ensure that vulnerable populations have continued access to adequate quality of care.